I-III-VI quantum dot and production method thereof

By using halide-based metal salt precursors to form the I-III-VI quantum dot nucleus and connect Group 17 elements on their surfaces, the problems of defective state emission of the I-III-VI quantum dots in the prior art and the full width of the wide half peak are solved, and high efficiency of visible light emission and high quantum efficiency are achieved, which is suitable for the application of display materials.

CN119698452APending Publication Date: 2025-03-25SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380059468.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-13
Filing Date
2023-06-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to develop a group I-III-VI quantum dot that is efficiently visible light emission and suitable for display materials, especially due to its defective state emission and wide half-maximum full width.

Method used

Improve the quantum efficiency of quantum dots and reduce defect state emission by forming group 11-13-16 quantum dot nuclei with group 11-13-16 on its surface, such as I.

Benefits of technology

It realizes efficient visible light emission, the area ratio of belt edge emission reaches 90% or more, the quantum efficiency reaches 20% or more, and the full width of the half peak is controlled at 40nm or less, which is suitable for the application of display materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698452A_ABST
    Figure CN119698452A_ABST
Patent Text Reader

Abstract

The present invention provides: I-III-VI quantum dots that emit highly efficient visible light and are thus suitable for use as a display material; and a method for manufacturing the quantum dot. The quantum dot according to the present invention comprises: a quantum dot core consisting of groups 11, 13, and 16; and a Group 17 element attached to a surface of the quantum dot core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to quantum dots with non-Cd compositions and methods for making the same, and more specifically, to I-III-VI based quantum dots and methods for making the same. Specifically, the present disclosure relates to I-III-VI based quantum dots for efficient visible light emission and methods for making the same. Background Art

[0002] Quantum dots are semiconductor particles with a size of tens of nanometers or less, and in contrast to bulk materials, they exhibit various properties according to the size and composition of the particles, and have optical and electrical properties that are not possessed by commonly used semiconductor materials. Quantum dots have better optical properties than fluorescent dyes based on organic materials, such as narrower half-maximum full width and higher emission intensity, and because they are made of inorganic-based materials, they have stability advantages. Due to these characteristics, quantum dots have attracted great attention as materials for color filters for displays, light-emitting diodes (LEDs), biosensors, lasers, and solar cells.

[0003] So far, compound semiconductors composed of elements from Group II-VI in the periodic table have been mainly studied, but in the case of high-efficiency quantum dots, they include substances that are harmful to the human body, such as Cd or Pb, which makes industrial utilization difficult. Compound semiconductors composed of Group III-V elements are represented by InP quantum dots, which have achieved a quantum efficiency of more than 95% and a narrow full width at half maximum (FWHM) of less than 40nm, which has led to the widest application in industry. When InP quantum dots are applied to displays, they are used as a light conversion layer on top of blue LEDs. Compared with red quantum dots, green InP quantum dots require a higher concentration because a difference in the absorptivity of the blue region is generated according to the particle size. The core diameter of green InP quantum dots is about 2 to 2.5nm, while the core diameter of red quantum dots exceeds 3nm, which results in a difference in absorptivity by several times. Therefore, compared with red InP quantum dots, green InP quantum dots require a light conversion layer with a concentration several times higher to achieve the same absorptivity.

[0004] I-III-VI group quantum dots are represented by CuInS2 (CIS) and AgInS2 (AIS), and compositions in which elements such as Ga are added to group III elements are typical. Since most of them exhibit emission from defect states rather than band edges, which results in a wide full width at half maximum (FWHM) of more than 100 nm, it is difficult to use them as display materials; therefore, they are used in solar cells or devices in the infrared region. In order to use I-III-VI group quantum dots as display materials, they need to have a narrow FWHM of less than 50 nm, a dominant band edge emission, and a high quantum efficiency. Summary of the invention

[0005]

Technical issues

[0006] The present disclosure aims to provide a quantum dot based on Group I-III-VI that emits highly efficient visible light and can be used as a display material, and a method for manufacturing the same.

[0007]

Technical solution

[0008] The quantum dot according to the present disclosure includes: a quantum dot core composed of Group 11-Group 13-Group 16; and a Group 17 element connected to the surface of the quantum dot core.

[0009] The Group 11 elements constituting the quantum dot core may be one or more selected from Cu, Ag and Au; the Group 13 elements may be one or more selected from In, Ga and Al; and the Group 16 elements may be one or more selected from S, Se and Te.

[0010] The ratio of the group 11 element to the group 13 element constituting the quantum dot core may be 1:1 to 1:10.

[0011] The 13 group elements constituting the above quantum dot core can be In 1-x Ga x Composition, where 0.2≤x≤0.9.

[0012] The quantum dots may also include ligands formed on the surface of the quantum dot core.

[0013] The ligand may be one or more selected from thiol compounds, amine compounds, phosphine compounds and metal salts.

[0014] Specifically, the ligand can be one or more selected from the following: butanethiol (1-butanethiol), hexanethiol (1-hexylthiol), octanethiol (1-octanethiol, OTT), undecanethiol (1-undecanethiol), decanethiol, dodecanethiol (1-dodecanethiol, DDT), hexadecanethiol (1-hexadecanethiol), octadecanethiol (1-octadecanethiol); amines, such as pentylamine, butylamine, hexylamine, heptylamine, octylamine, nonylamine, decylamine, didecylamine, tetradecylamine, hexadecylamine, octadecylamine, oleylamine (OLA), trihexylamine, trioctylamine (TOA), trilaurylamine; tributylphosphine oxide, tributylphosphine, trioctylphosphine oxide (TOPO), trioctylphosphine (TOP), ZnF2, ZnCl2, ZnBr2, ZnI2, GaF3, GaCl3, GaBr3, GaI3, AlF3, AlCl3, AlBr3 and AlI3.

[0015] The quantum dot core may include Ag, In, Ga, and S, and the Group 17 elements may be connected in the form of atoms or ions.

[0016] In an exemplary embodiment, the quantum dot core includes Ag, In, Ga, and S, and the Group 17 element is I.

[0017] The quantum dots according to the present disclosure may be free of defect states by using Group 17 elements.

[0018] The quantum dot may have an area ratio of 90% or more having band-edge emission over the entire PL spectrum of the quantum dot core.

[0019] The quantum efficiency (PL QY) of the quantum dot core can be 20% or more.

[0020] The emission center wavelength of the quantum dot core can be 520 to 540 nm.

[0021] The full width at half maximum (FWHM) of the quantum dot core may be 40 nm or less.

[0022] The size of the quantum dot core can be 3 to 6 nm.

[0023] Under 450nm blue light excitation, the quantum dot core can show 1×10 5 M -1 cm -1 or above the molar extinction coefficient.

[0024] The quantum dot according to the present disclosure may further include a shell on the quantum dot core, wherein the shell includes at least one of the Group 12 and Group 13 elements and at least one of the Group 16 elements.

[0025] In this case, the shell may be a system composition of two or more components including at least one of Al, Ga, or In and at least one of S or Se.

[0026] And, the shell may further include Zn.

[0027] The shell may be a multi-component single shell or multi-shell structure.

[0028] The area ratio of the band edge emission of the quantum dots including the shell over the entire PL spectrum may be 95% or more.

[0029] The quantum efficiency of the quantum dots including the shell may be 85% or more.

[0030] The emission center wavelength of the quantum dots including the shell may be 520 nm to 540 nm.

[0031] The full width at half maximum (FWHM) of the quantum dots including the shell may be 40 nm or less.

[0032] The size of the quantum dots including the shell may be between 5 and 10 nm.

[0033] Under 450nm blue light excitation, the quantum dots including the shell can show 1×10 5 M -1 cm -1 or above the molar extinction coefficient.

[0034] The method for manufacturing quantum dots according to the present disclosure includes: forming a group 11-13-16 quantum dot core using a halide-based metal salt precursor; and manufacturing a quantum dot comprising a group 17 element connected to the surface of the quantum dot core, wherein the group 17 element is provided by the halide-based metal salt precursor.

[0035] The halide-based metal salt precursor may include a Group 11 precursor and a Group 13 precursor, and the Group 17 element may be provided by the Group 11 precursor and the Group 13 precursor.

[0036] In this case, the Group 11 precursor and the Group 13 precursor may be at least one of AuF, AuCl, AuBr, AuI, CuF, CuCl, CuBr, CuI, AgF, AgCl, AgBr, AgI, InF3, InCl3, InBr3, InI3, GaF3, GaCl3, GaBr3 or GaI3.

[0037] The halide-based metal salt precursor may include a Group 11 precursor and a Group 13 precursor, and the Group 11 element and the Group 13 element of the halide-based metal salt precursor may be synthesized in a powder state or in a state in which they are dissolved in a solvent.

[0038] The halide-based metal salt precursor may further include a Group 16 precursor, and the Group 16 element of the Group 16 precursor may be fed in a state where it is dissolved in a solvent.

[0039] The solvent may be at least one of 1-octadecene (ODE), oleylamine (OLA), oleic acid (OA), dodecylamine, trioctylamine (TOA), or trioctylphosphine (TOP).

[0040] The method for manufacturing quantum dots according to the present disclosure may further include forming a shell on the quantum dot core, wherein the shell includes at least one of the Group 12 and Group 13 elements and at least one of the Group 16 elements.

[0041] The method for manufacturing quantum dots according to the present disclosure may further include feeding a ligand material to protect the surface of the quantum dots after forming the quantum dot core or forming the shell.

[0042]

Beneficial effects

[0043] According to the present disclosure, I-III-VI based quantum dots having a quantum dot core including Ag, In, Ga, and S (hereinafter referred to as AIGS quantum dots) may be fabricated to increase quantum efficiency and reduce defect state emission through surface control.

[0044] High-efficiency AIGS quantum dots fabricated according to the present disclosure can be synthesized into visible light emitting quantum dots with higher absorptivity than InP quantum dots.

[0045] Compared to AIGS quantum dots synthesized using acetate- or acetylacetone (acac)-based (i.e., non-halide-based) metal salt precursors, quantum dots synthesized using halide-based metal salt precursors according to the present disclosure include halogens on the surface and can therefore be synthesized as quantum dots with enhanced band edge emission and reduced defect state emission.

[0046] According to the present disclosure, it is possible to form AIGS quantum dot cores that exhibit very low levels of defect state emission, and synthesize quantum dots with high color purity after the core / shell step.

[0047] According to the present disclosure, the synthesis time can be reduced compared to existing methods.

[0048] According to the present disclosure, green quantum dots with high blue light absorption can be synthesized.

[0049] According to the present disclosure, quantum dots having a dominant band edge emission for use as display materials can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is a schematic diagram of a quantum dot according to an embodiment of the present disclosure.

[0051] Figure 2 is a flow chart of a method for making quantum dots according to an embodiment of the present disclosure.

[0052] Figure 3 is a flow chart of a method for fabricating AIGS / GS core / shell quantum dots according to an experimental embodiment of the present disclosure.

[0053] Figure 4 The emission spectra of AIGS quantum dot core and AIGS / GS core / shell quantum dots according to comparative examples are shown.

[0054] Figure 5 The emission spectra of AIGS quantum dot core and AIGS / GS core / shell quantum dots according to experimental examples of the present disclosure are shown.

[0055] Figure 6 I 3d XPS spectra of the AIGS quantum dot core according to the comparative example and the AIGS quantum dot core according to the experimental example of the present disclosure are shown.

[0056] Figure 7 1 is a transmission electron microscope (TEM) image of the AIGS quantum dot core and AIGS / GS core / shell quantum dots according to the comparative example and the AIGS quantum dot core and AIGS / GS core / shell quantum dots according to the experimental example of the present disclosure.

[0057] Figure 8 A histogram showing particle size distribution of the AIGS quantum dot core according to the comparative example and the AIGS quantum dot core according to the experimental example of the present disclosure is shown.

[0058] Fig. 9 Absorption spectra and absorbance spectra of InP quantum dots according to another comparative example and AIGS / GS core / shell quantum dots according to an experimental example of the present disclosure are shown. DETAILED DESCRIPTION

[0059] The accompanying drawings of this specification illustrate preferred embodiments of the present invention, and together with the detailed description of the present invention, are used to further understand the technical spirit of the present invention. Therefore, the present invention should not be interpreted as being limited to the contents described in these drawings.

[0060] The quantum dots and the production method thereof according to the present invention will be described in detail below with reference to the accompanying drawings. The accompanying drawings introduced subsequently are provided as examples to fully convey the spirit of the present invention. Therefore, the present invention is not limited to the accompanying drawings provided below and may be embodied in other forms. Unless otherwise defined, the technical terms and scientific terms used herein have the meanings commonly understood by ordinary technicians in the field to which the present invention belongs. In addition, the description of known functions and configurations that may unnecessarily obscure the essence of the present invention in the following description and drawings will be omitted.

[0061] Figure 1 is a diagram of quantum dots according to an embodiment of the present disclosure.

[0062] Figure 1 (a) is a diagram of a quantum dot core, and Figure 1 (b) is a diagram of core / shell quantum dots.

[0063] refer to Figure 1 (a) The quantum dot 10 according to an embodiment of the present disclosure includes a group 11-group 13-group 16 quantum dot core 20 and a group 17 element 30 connected to the surface of the quantum dot core 20 .

[0064] The quantum dot 10 is surface controlled by the Group 17 element 30 to increase quantum efficiency and reduce defect state emission. The quantum dot core 20 may be formed using a halide-based metal salt precursor, and the Group 17 element is provided from the halide-based metal salt precursor.

[0065] In the quantum dot core 20, the 11 group element can be at least one of Cu, Ag or Au, the 13 group element can be at least one of In, Ga or Al, and the 16 group element can be at least one of S, Se or Te. The quantum dot 10 can also include a ligand 40 located on the surface of the quantum dot core 20. The ligand 40 can include a thiol, such as 1-dodecyl mercaptan (DDT). In addition, in addition to DDT, the ligand 40 can include a variety of alkyl mercaptans, such as 1-octanethiol, hexadecyl mercaptan and decanethiol. In addition, the ligand 40 can be derived from the solvent used in the manufacturing method. In this article, the solvent can be at least one of 1-octadecene (ODE), oleylamine (OLA), oleic acid (OA), dodecylamine, trioctylamine (TOA) or trioctylphosphine (TOP). The 17 group elements can be connected in the form of atoms or ions. For example, the 17 group element is I. The 17 group element can be F, Cl, Br.

[0066] The quantum dot 10 according to the present disclosure may be free of defect states by means of group 17 elements. The quantum dot 10 includes group 17 elements, i.e., halogens on the surface, which results in enhanced band edge emission and reduced defect state emission. Therefore, over the entire PL spectrum of the quantum dot core 20, the area ratio of the band edge emission of the quantum dot 10 may be 90% or more. Since the area of ​​the band edge emission is relatively high, the quantum dot 10 may have a narrow half-maximum full width. The known I-III-VI based quantum dots include a variety of defects therein, and exhibit a variety of emissions through the defects. That is, defect state emission is dominant, and the emission spectrum is relatively wide. It can be used for lighting applications. In contrast, the quantum dot 10 according to the present disclosure presents an emission spectrum of a desired color (e.g., green) with a very narrow half-maximum full width due to the extremely dominant band edge emission, and can therefore be used for display applications.

[0067] For example, the quantum dot core 20 may include Ag, In, Ga, and S. In this case, the quantum dot core 20 may be referred to as an AIGS core.

[0068] The ratio of the group 11 element to the group 13 element in the quantum dot core 20 may be 1:1 to 1:10. Within this ratio range, the quantum dot core 20 may emit visible light between blue light and light yellow-green light. In addition, the group 13 element in the quantum dot core 20 may be In 1-x Ga x, where 0.2≤x≤0.9. The characteristic of controlling the ratio between the group 11 elements and the group 13 elements to control the wavelength, and controlling the composition ratio between In and Ga corresponding to the group 13 elements to control the ratio between the group 11 elements and the group 13 elements is a unique feature of the present disclosure. In this case, the emission center wavelength of the quantum dot core 20 can be 520 to 540nm. The center wavelength can correspond to green light emission and can be (for example) 530nm. The quantum dot 10 including the quantum dot core 20 can be used as a display material.

[0069] The quantum efficiency of the quantum dot core 20 may be 20% or more. This means that the quantum efficiency is at least 20%, and since defect states are removed by the Group 17 element, the quantum efficiency may be higher.

[0070] The full width at half maximum of the quantum dot core 20 may be 40 nm or less. In order to use I-III-VI based quantum dots as display materials, the quantum dot core 20 needs to have a narrow full width at half maximum of 50 nm or less. Since the full width at half maximum may be 40 nm or less, the quantum dot core 20 of the quantum dot 10 according to the present disclosure may be used as a display material.

[0071] The size of the quantum dot core 20 can be 3 to 6 nm. For example, the average size can be 5.5 nm. When the size of the quantum dot core 20 is outside the above range, it is not desirable in terms of quantum efficiency. The manufacturing method according to the present disclosure can be suitable for synthesizing quantum dot cores 20 of the above size.

[0072] Under 450nm blue light excitation, the quantum dot core 20 can show 1×10 5 M -1 cm -1 The molar extinction coefficient is higher than that of InP quantum dots. That is, the quantum dot core 20 can be a green quantum dot with high blue light absorption. As described above, according to the present disclosure, a quantum dot core 20, especially an AIGS core, can be formed that exhibits a very low level of defect state emission.

[0073] Reference Figure 1 (b), the quantum dot 10 according to an embodiment of the present disclosure may further include a shell 50 on the quantum dot core 20, the shell 50 including at least one of the group 12 elements and the group 13 elements and at least one of the group 16 elements. As described above, according to the present disclosure, a quantum dot core 20, especially an AIGS core, exhibiting a very low level of defect state emission can be formed, and a quantum dot 10 having high color purity can be synthesized after the core / shell step.

[0074] In this case, the shell 50 may be a system composition of two or more components including at least one of Al, Ga or In and at least one of S or Se. For example, the shell 50 may include Ga and S. In addition, the shell 50 may further include Zn. The Ga precursor for forming the shell 50 may be GaCl3, and the Zn precursor may be ZnCl2.

[0075] The shell 50 may be a single shell or a multi-shell structure of multiple components. The multi-shell may be a double shell or a triple shell. When the shell 50 is a double shell or a triple shell or a multi-shell, the shell 50 may have a gradually increasing band gap in the outward direction, i.e., as it moves away from the quantum dot core 20. The shell 50 has a high passivation effect. Therefore, the PL and quantum efficiency of the quantum dot 10 may be improved.

[0076] The area ratio of the band edge emission of the quantum dot 10 including the shell 50 over the entire PL spectrum may be 95% or more. Since the shell 50 is further included, the area ratio of the band edge emission may be increased compared to the quantum dot core 20.

[0077] The quantum efficiency of the quantum dot 10 including the shell 50 may be 85% or more. Since the shell 50 is also included, the quantum efficiency may be higher than the quantum efficiency of the quantum dot core 20. This means that the quantum efficiency of the quantum dot 10 is at least 85%, and the quantum efficiency of the quantum dot 10 may be further improved by engineering the band gap of the shell 50.

[0078] The size of the quantum dot 10 including the shell 50 may be 5 to 10 nm. The size of the quantum dot 10 is the result of the thickness of the quantum dot core 20 plus the shell 50. The quantum dot 10 including the quantum dot core 20 and further including the shell 50 may have an emission center wavelength of 520 to 540 nm, which is the emission center wavelength of the quantum dot core 20. Likewise, by further including the shell 50, the quantum dot 10 may have a half-peak full width narrower than the half-peak full width of the quantum dot core 20, and the half-peak full width may be 40 nm or less.

[0079] As described above, since the quantum dot 10 according to an embodiment of the present disclosure has an area ratio of band edge emission of 95% or more over the entire PL spectrum, band edge emission is observed, the full width at half maximum is as narrow as 40 nm or less, and the quantum efficiency is high, and therefore the quantum dot 10 can be used for display materials.

[0080] In the same manner as the quantum dot core 20, the quantum dot 10 including the shell 50 can exhibit 1×10 5 M -1 cm -1 or greater molar extinction coefficient.

[0081] Figure 2is a flow chart of a method for making quantum dots according to an embodiment of the present disclosure.

[0082] For example, a method for forming an AIGS quantum dot core will be described. In order to form the AIGS quantum dot core, a halide-based metal salt precursor is used (step S10).

[0083] As reference Figure 1 As described above, the group 17 element 30 of the quantum dot 10 is provided by a halide-based metal salt precursor. The halide-based metal salt precursor may include a group 11 precursor and a group 13 precursor, and the group 17 element 30 may be provided by the group 11 precursor and the group 13 precursor.

[0084] In this case, the Group 11 precursor and the Group 13 precursor may be at least one of AuF, AuCl, AuBr, AuI, CuF, CuCl, CuBr, CuI, AgF, AgCl, AgBr, AgI, InF3, InCl3, InBr3, InI3, GaF3, GaCl3, GaBr3 or GaI3.

[0085] The halide-based metal salt precursor may include a Group 11 precursor and a Group 13 precursor, and the Group 11 element and the Group 13 element of the halide-based metal salt precursor may be synthesized as a precursor in a powder state or in a state in which they are dissolved in a solvent.

[0086] The halide-based metal salt precursor may further include a Group 16 precursor, and the Group 16 element of the Group 16 precursor may be fed in a state where it is dissolved in a solvent.

[0087] The solvent may be at least one of 1-octadecene (ODE), oleylamine (OLA), oleic acid (OA), dodecylamine, trioctylamine (TOA), or trioctylphosphine (TOP).

[0088] Preferably, for example, the quantum dot core 20 can be synthesized by mixing an Ag precursor, an I precursor, a Ga precursor, an S precursor and sulfur with a solvent to prepare a mixed solution and heating the mixed solution. The heating of the mixed solution can be performed in multiple steps. First, degassing can be performed by heating at 120° C. Subsequently, the temperature can be raised to the growth temperature. In this case, N2 purging can be performed.

[0089] For example, the halide-based metal salt precursor of the AIGS quantum dot core 20, for example, AgI, InI3, GaI3 and a solvent are put into a three-necked flask and degassed at 120° C. or less for 30 minutes or more and then replaced with N2. Herein, the solvent may be ODE, OLA, OA.

[0090] Subsequently, a thiol-based ligand such as DDT and sulfur are fed as an S precursor, and after the temperature is raised to 260° C. or higher, for example, 280° C., the quantum dot nucleosynthesis reaction is completed within 10 minutes. In addition to DDT, the S precursor may include alkylthiols such as 1-octanethiol, hexadecanethiol, and decanethiol. Sulfur may be mixed with a solvent such as OLA. In addition to OLA, the solvent may include any other aliphatic amines such as dodecylamine, trioctylamine, and trioctylphosphine.

[0091] After forming the quantum dot core 20, the method may further include a step of lowering the temperature to 200° C. or less and feeding other ligand materials, such as trioctylphosphine (TOP) to protect the surface of the quantum dot core (step S15). This step is performed to remove defects that may exist on the surface of the quantum dot core 20. In addition to TOP, other ligand materials may include OTT and DDT. This step is performed to improve the efficiency and stability of the quantum dot core 20 by adsorption of other ligands.

[0092] According to this method, it is possible to synthesize Figure 1 (a) shows the quantum dot 10, and since the reaction is completed within 10 minutes, it can be synthesized in a shorter time than the 30 minutes or longer reaction time reported previously, and high reproducibility is achieved since complicated methods such as additional feeding are excluded.

[0093] Then, further reference Figure 2 , purify the formed quantum dot core 20 after precipitation using a polar solvent. The polar solvent can be ethanol, acetone. A centrifugal separator (9000rpm, 10 minutes) can be used to purify using a hexane / ethanol combination solvent, and then redispersed in a non-polar solvent to form a shell 50 (step S20). In this article, the non-polar solvent can be hexane, octane, toluene, chloroform, ODE, OLA.

[0094] The step of forming the shell 50 is a step of forming the shell 50 on the quantum dot core 20 , and the shell 50 includes at least one of the Group 12 elements and the Group 13 elements and at least one of the Group 16 elements.

[0095] For example, when forming a GaS shell, a Ga precursor and an S precursor may be fed, resulting in a reaction at 200° C. or higher, such as 240° C. for 2 hours, and after the temperature is reduced to 200° C. or lower, other ligand materials such as TOP, DDT may be fed to protect the surface of the core / shell quantum dots (step S25). The Ga precursor may be GaCl3, and the S precursor may be sulfur.

[0096] The shell may be formed using any other composition other than GaS, and may be formed by applying a suitable shell stock solution to the core. In addition, the step of forming the shell may be performed two or more times in succession. In this case, at least one of the type, concentration, or reaction temperature of the shell stock solution in each step and the time may be changed. In the second reaction, the temperature may be higher or the time may be longer. According to this method, it is possible to synthesize Figure 1 (b) shows a quantum dot 10 including a shell 50.

[0097] According to the present disclosure, in order to improve the quantum efficiency of AIGS quantum dots and reduce defect state emission, surface-controlled quantum dots can be manufactured. The high-efficiency AIGS quantum dots manufactured according to the present disclosure can be synthesized as visible light emitting quantum dots with higher absorptivity than InP quantum dots. According to the present disclosure, green quantum dots with high blue light absorptivity can be synthesized. Compared with AIGS quantum dots synthesized using metal salt precursors based on acetate or acetylacetone (i.e., non-halide-based), quantum dots synthesized using halide metal salt precursors according to the present disclosure include halogens on the surface, and thus can be synthesized as quantum dots with enhanced band edge emission and reduced defect state emission. According to the present disclosure, an AIGS core exhibiting a very low defect state emission level can be formed, and quantum dots with high color purity can be synthesized after the core / shell step. According to the present disclosure, the synthesis time can be reduced compared to existing methods.

[0098] Step S25 is a step of feeding a ligand material after the step of forming the shell 50 to protect the surface of the quantum dot 10. Other ligand materials such as TOP, OTT or DDT may be fed to remove defects that may exist on the surface of the quantum dot 10, thereby further improving the efficiency and stability of the quantum dot 10.

[0099] [Invention Mode]

[0100] Hereinafter, the present disclosure will be described in more detail by describing experimental examples.

[0101] Example

[0102] Figure 3 is a flow chart of a method for fabricating AIGS / GS core / shell quantum dots according to an experimental embodiment of the present disclosure.

[0103] To form AIGS quantum dot cores, AgI, InI3, GaI3, ODE and OLA were placed in a three-necked flask and vacuum degassed at 120°C for 30 min and then replaced with N2. Two experiments were performed in which the amount of Ag was 0.2 mmol and 0.4 mmol (Examples 1 and 2, respectively).

[0104] DDT and sulfur S (mixed with OLA) were fed and heated to 280° C., resulting in a reaction for 5 minutes. TOP was fed at 180° C., resulting in a reaction for 20 minutes to protect the surface of the quantum dot core. The manufacture of the quantum dot core was completed.

[0105] The quantum dot core was purified using a polar solvent, and the quantum dot core, GaCl3 and sulfur S (mixed with OLA) were placed in a three-necked flask, resulting in a reaction at 240°C for 2 hours to form a GaS shell. DDT and TOP were fed at 200°C, resulting in a reaction for 20 minutes to protect the surface of the core / shell quantum dots. Shell formation was completed.

[0106] Subsequently, the core / shell QDs were purified using polar solvents at room temperature for the next experiment and analysis.

[0107] Comparative Example

[0108] AIGS quantum dots were synthesized using non-halide based precursors. Silver acetate (AgC2H3O2), gallium acetylacetonate [Ga(C5H7O2)3], indium acetate, ODE and OLA were placed in a three-necked flask and vacuum degassed at 120°C for 30 minutes and then replaced with N2. Two experiments were performed in which the amount of Ag was 0.2mmol and 0.4mmol (Comparative Examples 1 and 2, respectively).

[0109] Subsequently, quantum dot cores and core / shell quantum dots were manufactured by the same method as in Example.

[0110] Characteristics evaluation

[0111] After precipitation of the synthesized QD core and core / shell QDs in a polar solvent, the absorption and emission properties were evaluated in the colloidal state by dispersion in a nonpolar solvent such as hexane.

[0112] Evaluation Tools

[0113] To analyze the emission properties of the synthesized nanocrystals (quantum dot core and core / shell quantum dots), the nanocrystals were dispersed in hexane and PL was measured at room temperature using a PL device (Darsa Pro-5200, PSI Co. Ltd) using a 500 W xenon arc lamp as the light source, and to analyze the size and shape of the dispersed nanocrystals, a high-resolution transmission electron microscope (HRTEM) (JEOL JEM 4010) was used, and to identify the elements on the particle surface attached to the core, X-ray photoelectron spectroscopy (XPS) (Thermo Scientific Inc., K-alpha) was used.

[0114] Experimental Results

[0115] Figure 4 It is based on the emission spectra of the AIGS quantum dot core and AIGS / GS core / shell quantum dots of the comparative example.

[0116] Figure 4 (a) shows the normalized emission (normalized PL) spectra of the cores of the quantum dots of Comparative Examples 1 and 2, and Figure 4 (b) shows the normalized emission spectra of the AIGS / GS core / shell quantum dots of Comparative Examples 1 and 2.

[0117] Table 1 shows the emission characteristics of the AIGS core and AIGS / GS core / shell synthesized according to the comparative example.

[0118] In Comparative Example 1 (0.2 mmol), the peak area of ​​defect state emission of the AIGS core is 20%:80% compared to the band edge emission and 1%:99%, which indicates that the band edge emission is rare and the defect state emission is dominant.

[0119] In Comparative Example 1 (0.2 mmol), the peak area of ​​defect emission of AIGS / GS core / shell is 80%:20% compared to band edge emission, which is 50%:50%. The ratio of defect emission is lower than that of the core, but the defect emission still has a high intensity, and this level is difficult to use in industrial applications.

[0120]

Table 1

[0121]

[0122]

[0123] Figure 5 The emission spectra of AIGS quantum dot core and AIGS / GS core / shell quantum dots according to experimental examples of the present disclosure are shown. Figure 5 (a) shows the normalized emission spectra of the cores of the quantum dots of Comparative Examples 1 and 2, and Figure 5 (b) shows the normalized emission spectra of the AIGS / GS core / shell quantum dots of Comparative Examples 1 and 2.

[0124] Table 2 shows the emission characteristics of the AIGS core and AIGS / GS core / shell synthesized according to the examples.

[0125]

Table 2

[0126] Synthesis using halide-based precursors Main peak (nm) Full width at half maximum (nm) Quantum efficiency (%) Ag 0.2mmol core (Example 1) 535 36 24.4 Ag 0.4mmol core (Example 2) 527 36.3 21 Ag 0.2mmol core / shell (Example 1) 533 36 86 Ag 0.4mmol core / shell (Example 2) 522 37 85

[0127] It was found that the quantum efficiency of AIGS / GS core / shell synthesized using halide-based precursors was 86% and 85% when the amount of Ag was 0.2 mmol (Example 1) and 0.4 mmol (Example 2), respectively. No emission due to defect states was observed, which means that defect states were removed.

[0128] When the general Figure 4 (a) with Figure 5 (a) When comparison is made, when the synthesis results using acetate- or acetylacetonate-based (i.e., non-halide-based) metal salt precursors are compared with the synthesis results using halide-based precursors according to the experimental embodiments of the present disclosure, the emission characteristics of the cores synthesized using the non-halide-based precursors show a major defect state emission (wavelength of 600 nm or above), while when the halide-based precursors are used, it can be seen that the defect state emission is significantly reduced and the band edge emission is the major emission wavelength (530 nm).

[0129] The shelling method was performed equally on non-halide based cores and halide based precursor cores. Figure 4 (b) with Figure 5 (b) When compared, even in the core / shell structure, quantum dots synthesized using non-halide based precursors exhibit much higher defect state emission than those synthesized using halide based precursors.

[0130] In order to use luminescent materials in display applications, materials with high color purity are required, and when the full width at half maximum is narrow, the color purity is high. When the defect state emission intensity is high, the full width at half maximum increases, and the color purity decreases, and it is difficult to use for industrial applications. Therefore, quantum dots synthesized using halide-based precursors are suitable for industrial applications due to significantly low defect state emission.

[0131] By using the surface analysis results of XPS, defect-free quantum dots according to the present disclosure can be observed.

[0132] Figure 6 I 3d XPS spectra of the AIGS quantum dot core according to the comparative example and the AIGS quantum dot core according to the experimental example of the present disclosure are shown.

[0133] like Figure 6 As shown, in contrast to the use of non-halide-based precursors, the XPS analysis results of the surface of the core synthesized using the halide-based precursor according to the present disclosure show that the halogen (I in the experimental example of the present disclosure) fed as a precursor is connected to the surface of the core (I3d5 / 2, I3d3 / 2 peaks are clearly observed). The halide fed as a precursor is connected to the surface.

[0134] It can be seen from the XPS results that using a halide-based precursor, the halide is attached to the surface of the quantum dot core, and by this method, defect states are removed. The halide removes dangling bonds present on the surface of the quantum dot core, thereby improving stability. The presence of dangling bonds in the PL characteristics leads to a decrease in quantum efficiency due to additional emission from electron trap sites and defect states, and according to the present disclosure, the removal of dangling bonds by halogen increases the total quantum efficiency, reduces defect state emission and improves band edge emission.

[0135] Figure 7 1 is a transmission electron microscope (TEM) image of the AIGS quantum dot core and AIGS / GS core / shell quantum dots according to the comparative example and the AIGS quantum dot core and AIGS / GS core / shell quantum dots according to the experimental example of the present disclosure.

[0136] like Figure 7 As shown, as a result of determining the particle size and distribution by TEM images of AIGS quantum dots synthesized using non-halide-based precursors and halide-based precursors, the average particle size in the core of the non-halide-based precursor is about 4.7 nm, while the average particle size in the core / shell is about 7.5 nm, and the quantum dots synthesized using the halide-based precursor have an average core size of about 5.5 nm and a core / shell size of 7.5 nm. However, the size of the core is not limited to the above size, and may vary between an average of 3 to 6 nm depending on the synthesis temperature.

[0137] Figure 8 is a histogram of particle size distribution of the AIGS quantum dot core according to the comparative example and the AIGS quantum dot core according to the experimental example of the present disclosure.

[0138] As a result of determining the size distribution of 50 particles randomly selected in the TEM image of the synthesized quantum dot core, it was found that the size distribution of the quantum dots synthesized by the non-halide-based precursor was 4.7 ± 0.7 nm, as Figure 8 (a), and the size distribution of quantum dots synthesized by halide-based precursors is 5.5 ± 0.4 nm, as shown in Figure 8 (b). Figure 8 (a) and Figure 8 As shown in (b), since the size distribution of quantum dots synthesized using a halide-based precursor is narrower than that of quantum dots synthesized using a non-halide-based precursor, it is found that they can be grown with a uniform size.

[0139] It was found that the distribution of cores and the distribution of core / shells had the same average size, but the synthesis using halide-based precursors had a uniform distribution. As described below, the uniformity of the particles can act as an important variable in the comparison of molar extinction coefficients (a measure of how much light 1M quantum dot particles can absorb). Since the number of moles of quantum dots is set according to the size of the quantum dot core, the higher the uniformity, the more accurate the value that can be obtained in the extinction coefficient calculation.

[0140] Fig. 9 (a) shows the absorption spectra of InP quantum dots according to another comparative example and AIGS / GS core / shell quantum dots according to an experimental example of the present disclosure, and Fig. 9 (b) shows their absorbance spectra.

[0141] In order to improve the low absorption rate of green InP quantum dots, as a comparison result of the molar extinction coefficient (F) measured under blue light (450 nm) excitation between InP quantum dots and AIGS quantum dots synthesized using halide-based precursors, it was found that AIGS quantum dots (i.e., 8.07 × 10 5 M -1 cm -1 ) has a larger 4 M -1 cm -1 ) is about 28 times or more higher in extinction coefficient. In this article, the extinction coefficient is calculated by the Beer-Lambert law.

[0142] Hereinabove, the present invention has been illustrated and described with reference to specific preferred embodiments; however, the present invention is not limited to the above-mentioned embodiments, and a person skilled in the art may make various changes and modifications without departing from the spirit of the present invention.

Claims

1. Quantum dots, comprising: Group 11-13-16 quantum dot cores; and A Group 17 element is attached to the surface of the quantum dot core.

2. The quantum dot of claim 1, wherein in the quantum dot core, the Group 11 element comprises at least one of Cu, Ag or Au, the Group 13 element comprises at least one of In, Ga or Al, and the Group 16 element comprises at least one of S, Se or Te. 3 . The quantum dot according to claim 1 , wherein the ratio of the Group 11 element to the Group 13 element in the quantum dot core is 1:1 to 1:

10.

4. The quantum dot according to any one of claims 1 to 3, wherein in the quantum dot core, the Group 13 element is In 1-x Ga x , where 0.2≤x≤0.

9.

5. The quantum dot according to claim 1, further comprising: A ligand is located on the surface of the quantum dot core. The quantum dot according to claim 5 , wherein the ligand comprises at least one of a thiol, an amine, a phosphine or a metal salt.

7. The quantum dot according to claim 5, wherein the ligand is 1-butanethiol, 1-hexanethiol, 1-octanethiol (OTT), 1-undecanethiol, decanethiol, 1-dodecanethiol (DDT), 1-hexadecanethiol, 1-octadecanethiol; an amine series, such as pentylamine, butylamine, hexylamine, heptylamine, octylamine, nonylamine, decylamine, didecylamine, tetradecylamine, hexadecylamine, octadecylamine, oleylamine (OLA), trihexylamine, trioctylamine (TOA), trilaurylamine; tributylphosphine oxide, tributylphosphine, trioctylphosphine oxide (TOPO), trioctylphosphine (TOP); ZnF2, ZnCl2, ZnBr2, ZnI2, GaF3, GaCl3, GaBr3, GaI3, AlF3, AlCl3, AlBr3 and AlI3, characterized in that The quantum dots include one or more of these. The quantum dot according to claim 1 , wherein the quantum dot core comprises Ag, In, Ga, and S, and the Group 17 elements are connected in the form of atoms or ions.

9. The quantum dot of claim 1, wherein the quantum dot core comprises Ag, In, Ga, and S, and the Group 17 element is I.

10. The quantum dot of claim 1, wherein defect states are configured to be removed by the Group 17 element.

11. The quantum dot according to claim 1, further comprising: A shell is disposed on the quantum dot core, wherein the shell includes at least one of Group 12 and Group 13 elements and at least one of Group 16 elements. 12 . The quantum dot according to claim 11 , wherein the shell is a system composition of two or more components, the system composition comprising at least one of Al, Ga or In and at least one of S or Se. The quantum dot of claim 12 , wherein the shell further comprises Zn. The quantum dot according to claim 11 , wherein the shell is a multi-component single shell or multi-shell structure.

15. A method for producing quantum dots, comprising: Forming a Group 11-13-16 quantum dot core using a halide-based metal salt precursor; and manufacturing a quantum dot comprising a Group 17 element attached to a surface of the quantum dot core, wherein the Group 17 element is provided by the halide-based metal salt precursor. 16 . The method for manufacturing quantum dots according to claim 15 , wherein the halide-based metal salt precursor comprises a Group 11 precursor and a Group 13 precursor, and the Group 17 element is provided by the Group 11 precursor and the Group 13 precursor.

17. The method for making quantum dots according to claim 16, wherein the Group 11 precursor and the Group 13 precursor are at least one of the following: AuF, AuCl, AuBr, AuI, CuF, CuCl, CuBr, CuI, AgF, AgCl, AgBr, AgI, InF3, InCl3, InBr3, InI3, GaF3, GaCl3, GaBr3 or GaI3.

18. The method for manufacturing quantum dots according to claim 15, wherein the halide-based metal salt precursor comprises a Group 11 precursor and a Group 13 precursor, and the Group 11 element and the Group 13 element of the halide-based metal salt precursor are synthesized in a powder state or in a state in which they are dissolved in a solvent. 19 . The method for manufacturing quantum dots according to claim 15 , wherein the halide-based metal salt precursor further comprises a Group 16 precursor, and the Group 16 element of the Group 16 precursor is fed in a state where it is dissolved in a solvent.

20. The method for producing quantum dots according to claim 18 or claim 19, wherein the solvent comprises at least one of 1-octadecene (ODE), oleylamine (OLA), oleic acid (OA), dodecylamine, trioctylamine (TOA) or trioctylphosphine (TOP).

21. The method for manufacturing quantum dots according to claim 15, further comprising: A shell is formed on the quantum dot core, wherein the shell comprises at least one of the Group 12 and Group 13 elements and at least one of the Group 16 elements.

22. The method for manufacturing quantum dots according to claim 21, after forming the quantum dot core or forming the shell, further comprising A ligand material is fed to protect the surface of the quantum dots.